1996
DOI: 10.1152/ajpcell.1996.271.4.c1032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on sarcoplasmic reticulum function and contraction duration in skeletal muscles of the rat

Abstract: The impact of aging on the Ca2+ pump function of skeletal muscle sarcoplasmic reticulum (SR) was investigated using SR-enriched membrane vesicles isolated from the slow-twitch soleus muscle (SM) and the relatively fast-twitch gastrocnemius muscle (GM) isolated from adult (6-8 mo old) and aged (26-28 mo old) Fischer 344 rats. In addition, isometric twitch characteristics of SM and GM were determined in situ in adult and aged rats under anesthesia. The rates of ATP-supported Ca2+ uptake by SM SR was markedly low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
56
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 29 publications
13
56
0
1
Order By: Relevance
“…Here we find that GH chronic treatment ameliorates the contractile function in aged skeletal muscle fibres by shifting the rheobase towards more positive values, typical of adults. This effect may be related to the GHinduced production of muscle insulin-like growth factor-1 (IGF-1), which in turn normalises intracellular Ca 2+ level by the restoration of the expression, turnover and activity of proteins involved in the contractile machinery (Narayanan et al, 1996;Renganathan et al, 1997;Ferrington et al, 1998;Wang et al, 1999). We also confirm the efficacy of longterm GH administration in the restoration of gCl and gK (De Luca et al, 1997).…”
Section: S Pierno Et Alsupporting
confidence: 67%
“…Here we find that GH chronic treatment ameliorates the contractile function in aged skeletal muscle fibres by shifting the rheobase towards more positive values, typical of adults. This effect may be related to the GHinduced production of muscle insulin-like growth factor-1 (IGF-1), which in turn normalises intracellular Ca 2+ level by the restoration of the expression, turnover and activity of proteins involved in the contractile machinery (Narayanan et al, 1996;Renganathan et al, 1997;Ferrington et al, 1998;Wang et al, 1999). We also confirm the efficacy of longterm GH administration in the restoration of gCl and gK (De Luca et al, 1997).…”
Section: S Pierno Et Alsupporting
confidence: 67%
“…Shin, et al demonstrated that in skeletal muscle CSQ is also involved in retrograde regulation of RyR function and store-operated Ca 2+ entry (SOCE) (Shin et al, 2003). Additional evidence is available that CSQ function is altered during muscle aging (Narayanan et al, 1996;Margreth et al, 1999). Thus, changes in the SR luminal Ca 2+ buffering capacity, or modification of the RyR release machinery from the luminal side, certainly plays an important role in the retrograde regulation of Ca 2+ signaling in striated muscle Brochet et al, 2005).…”
Section: Differential Properties Of Ca 2+ Sparks In Cardiac and Skelementioning
confidence: 99%
“…For example, a loss in the rate of calcium uptake activity (30-50%) in SR enriched vesicles has been observed that correlates with the extent (40%) of increase in relaxation times (147,(149)(150)(151)(152)(153).…”
Section: Aging In Skeletal Musclementioning
confidence: 99%
“…The few studies that have addressed possible alterations in expression levels of both RyR and DHPRs in senescent skeletal muscle report no age-related changes in receptor density based on either antibody detection by Western blots or binding of radioactive ligand, i.e., ryanodine or the dihydropyridine, PN-200-110 (143,146,147). However, another study suggested a preferential loss of DHPR density that resulted in an overall loss of DHPR: RyR coupling (148).…”
Section: Aging In Skeletal Musclementioning
confidence: 99%